Pengaruh Financial Immunity Perusahaan Terhadap Stock Return di Asia Menghadapi Masa Pandemi Covid-19 - Tri Nanda FSW; Irene Rini Demi Pangestuti (Jurnal Akuntansi dan Pajak, 2023)
The declining stock market conditions due to the Covid-19 pandemic are considered to be overcome by a strong financial position. The company is said to have good financial resilience with its ability to maximize its profitability, be able to compete with competitive stock prices, good management in fulfilling its obligations, and being socially responsible for the creation of a sustainable business environment. In this study, we try to examine the effect of Financial Immunity as measurenment in Return on Assets, Price Earning Ratio, Book-to-market Value, and Corporate Social Responsibility on Stock Return (Studies on Public Companies in Asia during the Covid-19 Pandemic). This study uses a quantitative approach, with multiple linear regression with panel data. The results of the study found that ROA and CSR can be used as measurenment for the company's Financial Immunity where both of them partially have a positive effect on Stock Return during the Covid-19 pandemic in Asia. Meanwhile, BMV and PER cannot be used as measurenment for the company's Financial Immunity where they partially do not have any influence on Stock Return during the Covid-19 pandemic in Asia. Meanwhile, simultaneously ROA, BMV, PER, and CSR as a measurenment for Financial Immunity have an effect on Stock Return during the Covid-19 pandemic